First pathologically confirmed case of concurrent primary renal cell carcinoma and metastatic lung adenocarcinoma in the same kidney - Tang, Hua; Zhang, Shengchun; Chen, Jian; Wang, Yongfu; Guo, Changping; Yu, Ting; Ye, Dechuan (Frontiers in Oncology, 2026)
BackgroundThe coexistence of a primary tumor and a histologically distinct metastasis within the same organ presents a rare diagnostic dilemma, challenging the classical criteria for multiple primary malignant neoplasms (MPMNs). We report the first pathologically confirmed case of synchronous primary clear cell renal cell carcinoma (RCC) and metastatic lung adenocarcinoma within the same kidney.Case descriptionA patient with tumors in the left lung, right femur, and left kidney underwent laparoscopic left nephrectomy. Postoperative pathology surprisingly identified two distinct lesions: a primary clear cell RCC and a metastatic adenocarcinoma. Subsequent biopsies confirmed the lung as the primary source of the adenocarcinoma (EGFR L858R mutation). The patient was treated with furmonertinib and radiotherapy.ConclusionThis case underscores the critical importance of histopathological confirmation in complex presentations. It illustrates that even with imaging suggestive of a single primary carcinoma, meticulous pathological evaluation is essential to uncover synchronous MPMNs, thereby guiding precise therapy. The patient demonstrated a positive response to targeted treatment.